Effect of feeding management on faecal glucocorticoid metabolite concentrations as a measure of physiological stress in the African Elephant (Loxodonta africana) - Webb, E.C. (Edward Cottington) (University of Pretoria, 2025)
Dissertation (MAgric (Animal Science Production Physiology))--University of Pretoria, 2024.